The secret of reducing turnover intention: Evidence from Indonesia - Furtasan Ali Yusuf; Widodo Widodo (Cogent Business & Management, 2023)
Turnover still occurs in various organizations, including both profit and non-profit. Accordingly, a study of turnover intention (TI) to detect and anticipate its prevalence among employees is urgently needed. This study explored the impact of psychological capital (PsyCap) and emotional intelligence (EI) on TI mediated by organizational commitment (OC). A survey-operated causal design with a Likert-scale questionnaire was employed to gather data from 439 honorary private school teachers in Indonesia. Structural equation modeling analysis showed that EI and OC negatively affected TI, PsyCap positively affected OC, and PsyCap negatively affected TI through OC. However, PsyCap did not significantly affect TI, EI did not significantly affect OC, and EI did not significantly affect TI mediated by OC, which is inconsistent with previous studies. These inconsistencies create a research gap that requires scientific clarification and confirmation in future research. Practitioners can use this study's results to reduce TI through the PsyCap, EI, and OC perspectives.
Keywords: 650; behavioral science; educational management; HRM; organizational psychology; social science